The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5005/jp-journals-10005-1227
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Alpha Amylase as a Noninvasive Biomarker for Dental Fear and Its Correlation with Behavior of Children during Dental Treatment

Abstract: Objective: Objectives of our studies were to predict dental fear in a child patient depending on salivary alpha amylase (sAA) level before and after dental treatment and to evaluate correla­tion of later with behavior of child patient during dental treatment.Materials and methods: Seventy-seven children between age of 5 and 12 years were divided in three groups. Group 1 consisted of 25 school children who did not undergo any dental treatment. Groups 2 and 3 underwent dental treatment without and with local ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Noorani et al observed no differences in SAA activity in 5 to 12 year old children in both genders (11). Nonetheless, in a research using a corneal transplant surgery video as stressful stimuli, the researchers obtained a more increase in SAA level in younger men (12).…”
Section: Iranmentioning
confidence: 96%
See 1 more Smart Citation
“…Noorani et al observed no differences in SAA activity in 5 to 12 year old children in both genders (11). Nonetheless, in a research using a corneal transplant surgery video as stressful stimuli, the researchers obtained a more increase in SAA level in younger men (12).…”
Section: Iranmentioning
confidence: 96%
“…However, positive relationship between them and the dental anxiety remains unclear. Salivary alpha amylase (SAA) was considered as a suitable biomarker of sympathetic nervous system activity in recent years (11).…”
Section: Introductionmentioning
confidence: 99%
“…The role of salivary α-amylase in stress was investigated, and it was demonstrated that stress causes a significant increase in salivary α-amylase levels (24). Dental treatment itself can induce anxiety and fear in children, and these emotions cause significantly increased levels of salivary α-amylase immediately after dental treatment (25). Also salivary α-amylase was suggested as a marker of the autonomic nervous system response to stress in youth and adults (26).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the autonomic nervous system has a strong influence over the salivary glands and controls the secretion of sAA [7]. It is considered a reliable biomarker of stress and is preferred as a noninvasive procedure among several other methods because it does not cause distress to the subject [2,[7][8][9]. The activity of sAA is reported to increase during distress and decrease during comfort [10].…”
Section: Introductionmentioning
confidence: 99%